2011
DOI: 10.1038/cmi.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

The response of intestinal stem cells and epithelium after alemtuzumab administration

Abstract: Intestinal stem cells may have important roles in the maintenance of epithelial integrity during tissue repair. Alemtuzumab is a humanized anti-CD52 lymphocytic antibody that is increasingly being used to induce immunosuppression; intestinal barrier function is impaired during treatment with alemtuzumab. We investigated the response of intestinal stem cells to epithelial damage resulting from alemtuzumab treatment. Intestinal epithelial cell loss and abnormal Paneth cell morphology were found following a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Evidence stemming from a cynomolgus monkey model indicated that the intestinal barrier may be disrupted during alemtuzumab treatment [106]. In macaques monkeys, a single dose of alemtuzumab resulted in (i) intestinal epithelial cell loss, (ii) increased apoptosis in the villi, and (iii) an abnormal Paneth cell morphology [107]. Mouse anti-CD52 mAb also resulted in increased numbers of IELs undergoing apoptosis and disrupted intestinal barrier function in mice [108].…”
Section: Alemtuzumabmentioning
confidence: 99%
“…Evidence stemming from a cynomolgus monkey model indicated that the intestinal barrier may be disrupted during alemtuzumab treatment [106]. In macaques monkeys, a single dose of alemtuzumab resulted in (i) intestinal epithelial cell loss, (ii) increased apoptosis in the villi, and (iii) an abnormal Paneth cell morphology [107]. Mouse anti-CD52 mAb also resulted in increased numbers of IELs undergoing apoptosis and disrupted intestinal barrier function in mice [108].…”
Section: Alemtuzumabmentioning
confidence: 99%
“…Gut I/R can induce a significant reduction in T-cell numbers and variations in lymphocyte phenotypes in intestinal mucosa, leading to enteric bacterial translocation and development of septic complications (144, 145). Depletion of intestinal mucosal lymphocytes induced by Campath-1H could cause dysbiosis of gut microbiota (128, 146, 147) and disruption of intestinal epithelial barriers (148, 149). Similar to the observations, severe impairment of gut barrier integrity was also seen in intestinal transplanted patients receiving Campath-1H administration (150, 151), which might be a major reason for high incidence of infectious complications after small bowel transplantation.…”
Section: Microbiota-immune Interaction and Gut-derived Infectionmentioning
confidence: 99%
“…The transformation of leucine-rich repeat-containing G protein-coupled Receptor 5 (Lgr5 + ) stem cells drives intestinal neoplasia in the Apc flox/flox mouse model, indicating that Lgr5 + crypt stem cells are the cell-of-origin of cancer (1). Colon cancer has been suggested to follow a cancer stem cell (CSC) hierarchical model (2,3). Although cycling Lgr5 + stem cells fuel the rapid turnover of the adult intestinal epithelium (4,5), and its properties are not shared by other crypt cells (6,7), the role of Lgr5 + cells in colorectal cancer pathogenesis has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify the properties of Lgr5 + cells at the initiation stage of colon tumorigenesis because transformation of Lgr5 + stem cells is an extremely efficient route towards initiating intestinal cancer (1). Recently, DNA damage responses in Lgr5 + cells have been reported (2,8,9), however, to date, colonic Lgr5 + cytokinetics have not been examined in the context of an alkylating agent induced-DNA damage model of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%